Simultaneous effect of disease and toxicant on a plant population: a model - Chauhan, Sudipa; Misra, Om prakash; Dhar, Joydip (Global Journal of Mathematical Analysis, 2014)
In this paper, we have studied the effect of disease separately on the plant population and the simultaneous effect of diseaseand toxicant on plant population. The disease is caused to the plants by vector population and toxicants are effecting the total plant density directly through air. The local and global stability conditions for both the models have been derived and numerical simulation is done using MATLAB software. Keywords: Plant population, Vector population, Disease, Toxicant, Stability.